ANALISIS KOMITMEN ORGANISASIONAL TERHADAP KEINGINAN BERPINDAH - WARSITO KAWEDAR; IKA JUNIARTA LUBIS (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2009)
The research aims to test multiple dimensions from organizational commitment (affectiveand continuance commitment) in its relation to important organizational consequence, whichis job satisfaction and turnover intention. This research is consistent with Ketchand andStrawser (1998) and also Kadir (2003). These are difference in this research from formerresearch in term of sample used. Respondents are auditors at state auditor agency (BPKP)of Central Java and North Sulawesi. Hypothesis testing used Structural Equation Modeling(SEM). Analysis result of the affective commitment has positive effect on job satisfaction,continuance commitment has negative effect on job satisfaction, affective commitment hasnegative effect on turnover intentions, continuance commitment has negative effect on jobsatisfaction, and job satisfaction has negative influence to turnover intentions. This resultconsistent with research done by Ketchand and Strawser (1998) and Kadir (2003). Thisresearch gives contribution to research expanding depicting requirements to apply approachmultidimensional to research of commitment organizational. Multidimensional approach tocommitment organizational gives more accurate understanding about individual involvementin its organization.Keywords : Organizational Commitment, Job Satisfaction, And Turnover Intention